Potensial of Lost Circulation Zones in RJ Well, CP Field by Calculating Hydrostatic, Formation and Fracture Pressure - Reynaldy Julio; M. Nur Mukmin; Firdaus; Afrida; Aprilino Alfa Kurmasela; Darmiyati, Iin; Annisa Efidiawati (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study aims to analyze the potential of lost circulation zones in the RJ well at the CP field by calculating hydrostatic pressure, formation pressure, and formation fracture pressure. Lost circulation occurs when drilling fluid is lost into the formation, which can disrupt the drilling process. In this study, calculations were made for hydrostatic pressure, formation pressure, and formation fracture pressure at various depths of the well. The results show that at a depth of 741 ft, the hydrostatic pressure is 330.22 psi, formation pressure is 318.66 psi, and formation fracture pressure is 982.88 psi. Meanwhile, at a depth of 9517 ft, the hydrostatic pressure reaches 5438.78 psi, formation pressure is 5290.31 psi, and formation fracture pressure is 7237.24 psi. The significant difference between hydrostatic pressure and formation pressure leads to the occurrence of lost circulation. In conclusion, the potential for lost circulation in the RJ well is caused by hydrostatic pressure being higher than formation pressure. This study provides important insights into the factors influencing lost circulation and is expected to serve as a reference for future drilling operations.